Seed germination and seedling morphology of Artabotrys hexapetalus - TRI HANDAYANI (Nusantara Bioscience, 2017)
Handayani T. 2017. Seed germination and seedling morphology of Artabotrys hexapetalus. Nusantara Bioscience 9: 23-30. Artabotrys hexapetalus (L.f.) Bhandari (kenanga tanduk) is a fragrant, shrubby climber belonging to the Annonaceae family. In Indonesia, it is known as â€œkenanga tandukâ€. It is a commercial ornamental plant due to its beautiful, aromatic flowers. This plant is also used in the perfume industry and in traditional medicine. It can be naturally propagated from seeds. However, it takes a long time to germinate. The research reported here aimed to determine the seed germination process, early seedling development, and seedling morphology of A. hexapetalus seeds planted under controlled conditions in Bogor Botanic Gardens. Ninety seeds were planted in a sand medium. The timing of germination, its characteristic pattern and the morphology of young emerged seedlings were observed and recorded. The seed characters were observed by using a microscope and camera. The results confirmed that A. hexapetalus seeds take a long time to germinate. Different periods of fruit maturation, small immature embryos, hard seed coat and hard endosperm texture are some of the factors that cause its seed to take a long time to germinate. The hard seed is due to the presence of exotesta, mesotesta and endotesta layers in the seed coat, as well as to the ruminate endosperm shaped like a wide plate and hard like glass (glass-like endosperm). The earliest seed germination occurred 159 days after sowing. The duration of seed germination from planting to last germinated seed took as long as 238 days. However, final seed viability reached 80%, with the speed of germination from sowing until the time of germination on a given day ranging from 0.01 to 0.08% per day. The type of seedling emergence is Phanerocotylar-Epigeal- Foliaceous (PEF). The seed germination process of A. hexapetalus from radicle appearance until the first open leaf can be divided into six stages; i.e. radicle growing phase, radicle and hypocotyl growing phase, hypocotyl emergent phase, cotyledon emergent phase, cotyledon opening phase and the first leaf opening phase. The pair of cotyledons look like true mature leaves and are firmly attached, not shedding easily.